The impact of Corruption on Private Investment in the MENA region: An Empirical Study on the period of 1996-2023 - El Regdawy, Mohamed A (AUC Knowledge Fountain, 2026)
This study aims to examine and understand empirically the impact of corruption on private investment in the MENA region during the period of 1996-2023, as private investment is a key enabler for sustainable economic growth. To better understand such a relationship, a Pooled Mean Group estimator was implemented to figure out this relationship in both the short run and long run. The findings confirm that in the long run, within the context of MENA, corruption was used as a tool to overcome the lack of quality in the regulations that were supposed to enable the role of the private sector. This finding is aligned with the Grease the Wheels Hypothesis, which shows that corruption acts can be an enhanced and efficient tool to remove all the government-imposed rigidities, including the escape from the impact of the bad public policies. The study concludes with policy alternatives that are more relevant to enhancing the quality of the regulatory frameworks, as it serves as a causal root for the corruption.